UNIT 5.6 Models of Inflammation: Carrageenan Air Pouch. Issue 1 (18th March 2016) - Duarte, Djane B.; Vasko, Michael R.; Fehrenbacher, Jill C.
Abstract : The subcutaneous air pouch is an in vivo model that can be used to study the components of acute and chronic inflammation, the resolution of the inflammatory response, the oxidative stress response, and potential therapeutic targets for treating inflammation. Injection of irritants into an air pouch in rats or mice induces an inflammatory response that can be quantified by the volume of exudate produced, the infiltration of cells, and the release of inflammatory mediators. The model presented in this unit has been extensively used to identify potential anti‐inflammatory drugs. © 2016 by John Wiley & Sons, Inc.